A Gender-Based Linguistic Patterns in Quora Apps: A Comparative Study - Candra Dewi, Tinara; Widyawati, Wiwin; Rochmahwati, Pryla; Khasanah, Nurul (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
There is a wide variety of interrelated social media platforms. Gender orientation can affect preferences for language use in particular social media, especially Quora, which is famous as a medium for collecting questions and answers on specific topics. Breaking new ground, this study uniquely juxtaposes gender orientation with linguistic preferences on Quora, an unexplored research area. This content analysis design employed textual data posted by Quora users in the